Desenvolvimento de uma linguagem baseada em ontologias para geração de ações de futebol de robôs - Maia, Felipe Pedrozo (2017)
The advances in robotics for everyday life are subject of research in several fields such as health, entertainment and education. Specifically, the research and development of robots for the dispute of soccer matches has gained strength with the RoboCup league. The development of robot behaviors for soccer matches can lead to applications in several areas of knowledge, becoming a key aspect in the evolution of robotics in any application. For the development of behaviors, programming languages are used to create algorithms that determine the robot’s actions. It is noticeable that this is not a trivial task, specially when considered that several programming languages may be used. The current work approaches the creation of an ontology for the robot soccer domain, as a way of describing in a semantic and logic form the set of behaviors of a robot. Furthermore, the ontology facilitates the process of sharing the rules created under this domain. Another topic of this work is the development of a language for programming robot behaviors in the context of soccer matches. The programming language, called Maia, is based in the RS language due the fact that it is simple and has a format “Condition -> Action” that facilitates reasoning. In this context, the goal of the programming language is to ease the development of behavior for robots, once it is a complex task for non-experts, where the time necessary to learn a programming language can be limiting factor. Hence, the ontology and the Maia programming language complement themselves becoming an important factor in the creation of behaviors, once that it is possible to map each scenario and implement it taking into consideration the dynamism of the game.